OSTEOPETROSIS - A SURVEY OF 17 CASES - Burki, Mumtaz Khan; Wazir, Mehr Dil Khan; Qayum, Iftikhar (Journal of Ayub Medical College Abbottabad, 1996)
This is a retrospective survey of 17 children with osteopetrosis admitted in paediatrics ward from 1990 to 1995. Their clinical data, radiographs. laboratory data c£ histories were analyzed. All of them were male with age range from 1 month to 5 years. 80% of patients had a history of parental consanguinity. All of them had moderate to severe anaemia and failure to thrive as their presenting symptoms. Other predominant associated features were stuffy nose with depressed nasal bridge (95%), hepatosplenomegaly (90%) and increase in size of head (80%). Neurological complications such as visual loss (80%) and deafness (40%:) were also observed. Not a single fracture was observed. The diagnosis of osteopetrosis was made by chance, radiologically. Treatment in all patients was symptomatic. No curative treatment was available. Mortality was high due to repeated infections and bleeding. The possibility of a new subtype of malignant recessive osteopetrosis is discussed.